PENGEMBANGAN E-BOOK BERBASIS BOOK CREATOR UNTUK MEMFASILITASI KEMAMPUAN BERPIKIR KREATIF SISWA SMK - Titasni; Risnanosanti; Fitriani, Apriza (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to produce and describe a Book Creator-Based E-Book to Facilitate Creative Thinking Skills in Vocational High School Students. This research is a developmental research using the ADDIE model, which consists of five development stages: Analysis, Design, Development, Implementation, and Evaluation. The subjects were 11th-grade students of SMK Negeri 2 Bengkulu City. The instruments used were material and design validation sheets, practicality questionnaires, student response questionnaires, and mathematical literacy tests. This research produces a Book Creator-Based E-Book that can Facilitate the Creative Thinking Skills of Vocational High School Students on the Opportunity material with Permutation and Combination sub-subjects in a ppt format that can be easily accessed by students. The description of the material presented in the ebook uses the book creator framework. The validity criteria by the expert team are seen from the results of material validation with a validity level in terms of material of 80% at the valid category level, and the results of design validation with a validity level in terms of design of 100% at the very valid category level. effectiveness is carried out after students study the Permutation and Combination material using the book creator in the learning process during the field trial. The results of the assessment of the effectiveness of the book creator using this student response questionnaire are 90.93% with a very effective category.